Решите уравнения: (x+1)(x^{2}-x+1)-x(x+2)(x-2)=3

настя14о настя14о    3   07.03.2019 13:30    69

Ответы
лиана247 лиана247  24.05.2020 02:58
FUpp FUpp  24.05.2020 02:58

Первое уравнение:

x^3+1-x*(x+2)*(x-2)-3=0

x^3+1-(x^2+x*2)*(x-2)-3=0

x^3+1-(x^3-x*4)-3=0

x^3+1-x^3+x*4-3=0

1+x*4-3=0

-2+x*4=0

Решаем относительно x:
x=2/4=1/2~0.5.

 

Второе уравнение:

X^3-8-(2*X-4)*X=0

X^3-8-(2*X^2-4*X)=0

X^3-8-2*X^2+4*X=0

 

А вот дальше решить не получается(

 

 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра